Implementasi Pelatihan Qiro’ah Dalam Meningkatkan Kemahiran Membaca Al-Qur’an Terhadap Santri TPQ Al-Halim Desa Sambungrejo Sukodono Sidoarjo - Amir Bandar Abdul Majid; M. Amin; Tri Marfiyanto; Fadlilla Maghfiroh; Muhammad Zakki; Muhammad Amin; Didit Darmawan; Masrur Huda; Asyhari Asyhari (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
The Qur'an is the sacred text of Muslims that serves as a guide in life. Therefore, in reciting the Qur'an, it is necessary to understand from the letters to the reading rules. In the process of learning to read the Qur'an, teaching methods have a very crucial role, and there are several approaches that have been implemented to facilitate learning. The method is chosen as a means and tool of teaching transformation to achieve the desired goal. The goal of qiroah training is to facilitate students in improving their skills in reading the Qur'an, especially among TPQ AL-HALIM students. In addition, qiroah training aims to instil students' appreciation of Islamic cultural arts, develop students' talents and interests in the field of reciting the Qur'an, and promote a sense of independence.